Nickel diatom carbon dioxide electroreduction catalyst with wide voltage window and preparation method of nickel diatom carbon dioxide electroreduction catalyst
By designing atomically dispersed Ni diatomic active sites and uncoordinated N-doped structures, a nickel diatom carbon dioxide electroreduction catalyst with a wide voltage window was prepared, which solved the problems of selectivity and limited potential range of CO2 electrochemical reduction technology in the prior art, and achieved an efficient and stable CO2 reduction reaction.
Patent Information
- Application Number
- CN202411851824.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing CO2 electrochemical reduction technology can only achieve high selectivity in a narrow potential range, limiting its practical application, especially when the output voltage of the solar cell fluctuates.
By designing the atomically dispersed Ni diatomic active sites and their coordination structures, combining the uncoordinated N-doped structure, a nickel diatom carbon dioxide electroreduction catalyst is prepared using an efficient precursor gas diffusion strategy.
It achieves high activity and high CO selectivity in a wide potential window. The CO Faraday efficiency can reach 92.78% at low voltage, and maintains high CO selectivity in an ultra-wide voltage window, achieving industrial-grade current density and having good catalytic stability.
Smart Images

Figure CN119913550A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material technology, and specifically relates to a nickel diatomic carbon dioxide electroreduction catalyst with a wide voltage window and a preparation method thereof Background Art
[0002] CO2 electrochemical reduction technology (CO2RR) is an effective way to convert CO2 into high-value chemicals such as CO, CH4, etc. Its main advantage is that it can be combined with sustainable energy conversion (such as solar cells) and the generated electricity can be stored in high-value chemicals in chemical form. However, in practical applications, the output voltage of solar cells fluctuates due to changes in factors such as temperature and light intensity, and highly selective CO2RR can only be achieved within a narrow potential range, which greatly limits its practical application. Therefore, it is of great significance to develop highly selective and efficient catalysts within a wide potential range.
[0003] Studies have shown that MN x C (M stands for metal) configurations, such as FeN4C, NiN4C, CuN4C, etc., are beneficial for the electrocatalytic conversion of CO2 to CO. Considering the specific energy barriers of *COOH formation and CO desorption, Ni single atoms have attracted much attention due to their high selectivity. In addition, due to the synergistic effect between adjacent active sites, the construction of diatomic metal sites can exhibit efficient catalytic performance. At the same time, through the regulation of its coordination structure, its catalytic activity at low potential and selectivity at high potential can be further improved. Therefore, by designing atomically dispersed Ni active sites and their coordination structures, it is expected to develop efficient and highly selective CO2 electrochemical reduction catalysts with a wide voltage window. Summary of the invention
[0004] The object of the present invention is to provide a nickel diatomic carbon dioxide electroreduction catalyst with a wide voltage window and a preparation method thereof.
[0005] The nickel diatomic carbon dioxide electroreduction catalyst with a wide voltage window proposed in the present invention is prepared by an efficient precursor gas diffusion strategy. By introducing an appropriate amount of uncoordinated N doping structure, the method for preparing the Ni diatomic catalyst is applied to CO2RR, which can achieve high intrinsic activity while inhibiting the hydrogen evolution reaction, thereby achieving high activity and high CO selectivity in a wide potential window. When the reduction voltage is only -0.25V (vs.RHE), FE CO The selectivity of CO can reach 92.78% and the ultra-wide voltage window of about 1.2 V can maintain high CO selectivity and achieve industrial-grade current density (100 mA / cm 2 In addition, the electrocatalyst also has good catalytic stability. In the constant voltage test for 10 hours, the product FECO Basically maintained above 97%.
[0006] To achieve the above object, the present invention is implemented by the following technical solutions, which are specifically implemented according to the following steps:
[0007] Step 1, cutting a certain size of nickel (Ni) foam, soaking it in anhydrous ethanol for ultrasonic cleaning, then rinsing it with deionized water and drying it in an oven for later use.
[0008] Step 2: placing a certain amount of dicyandiamide (DCD) upstream of the tube furnace and placing nickel foam downstream of the tube furnace.
[0009] Step 3, using argon (Ar) as a protective gas, the tube furnace is heated to a certain temperature at an appropriate heating rate, and the temperature is maintained at the growth temperature for 0.2 to 3 hours, and then naturally cooled to room temperature.
[0010] Step 4, collecting the product after the reaction, grinding it thoroughly, and then soaking and etching the nickel foam with HCl.
[0011] Step 5, after the etching is completed, the product is taken out and washed thoroughly with deionized water, centrifuged at high speed, and collected to obtain the Ni diatomic catalyst after being completely dried.
[0012] The technical solution of the present invention also has the following characteristics:
[0013] In step 1, the chemical purity of the nickel foam is 98% to 99.999%, and the cutting size can be determined according to the diameter of the tubular furnace.
[0014] In step 2, the dicyandiamide has a purity of 98% to 99.999%.
[0015] In step 3, the argon gas flow rate is 30-300 sccm. The heating rate of the tube furnace is 5-20° C. / min.
[0016] In step 4, the growth temperature is 600° C. to 1000° C. and the holding time is 0.2 to 3 hours.
[0017] In step 5, the acid etching uses 1-5 mol / L hydrochloric acid, the acid etching temperature is 60-80° C., and the acid etching time is 48-100 hours.
[0018] The present invention uses scanning electron microscopy (SEM) to characterize the morphology of the catalyst. Figure 1 As shown, hollow carbon nanotube structures can be observed. High-angle annular dark-field scanning transmission electron microscopy was then used to further characterize the microstructure of the catalyst, as shown in Figure 2 , showing a typical N-doped carbon nanotube bamboo-like structure and a hollow tubular structure without Ni particles. Figure 3 As shown in Figure 1, a large number of Ni atoms are dispersed on the carbon support, and diatomic Ni sites marked by red boxes can be observed, proving that the catalyst has a diatomic structure. EDS analysis shows that the distribution of the three elements C, N, and Ni is uniform (e.g. Figure 4 ), no obvious particle accumulation phenomenon was found, which further proves that the Ni diatomic catalyst can be successfully prepared by the method of the present invention. In addition, the phase composition of the catalyst was analyzed by XRD, such as Figure 5 As shown in the figure, obvious characteristic peaks of graphite and metallic nickel appeared in D-Ni-700, and the characteristic peak intensity of nickel metal in D-Ni-700-H decreased significantly after acid etching. Figure 6 As shown in the Raman spectrum of the sample, there are two graphite characteristic peaks, I D / I G is 1.09, proving that the carbon hexagonal rings of the catalyst carrier carbon nanotubes contain a large number of defect structures. Further XPS characterization of the material, such as Figure 7 As shown in Figure 1, the fine structure analysis of the N1s orbital shows that its N doping types include pyridinic nitrogen (398.4 eV), Ni-N (399.1 eV), pyrrolic nitrogen (400.5 eV), graphitic nitrogen (401.3 eV) and oxidized nitrogen (403.1 eV). The spectrum of the Ni 2p orbital (such as Figure 8 )Compared with Ni 0 (853.5eV) and Ni 2+ (856 eV), Ni 2p of the catalyst 3 / 2 The binding energy is in between, proving that the valence state of Ni atoms in each sample is between 0 and +2, which is consistent with the characteristics of atomic-level dispersion. Subsequently, XAS was used to deeply analyze the coordination structure of Ni diatoms, and K-edge X-ray near-edge structure absorption (XANES) spectroscopy analysis ( Fig. 9 ), proving that the near-edge absorption position of D-Ni-700-H is located between nickel foil (Ni Foil) and nickel oxide (NiO), and closer to nickel phthalocyanine (NiPc) with a NiN4 coordination structure. This indicates that the valence state of Ni atoms in D-Ni-700-H is between 0 and +2, which is consistent with the results of Ni 2p orbital analysis in XPS. After Fourier transformation of the extended X-ray absorption fine structure (EXAFS), the data spectrum in R space is obtained, as shown in the figure. Fig.10 As shown in the figure, compared with the characteristic peaks of Ni-Ni and Ni-N in nickel foil and nickel phthalocyanine, it can be seen that there are Ni-Ni and Ni-N coordination environments in D-Ni-700-H. In order to observe the composition of the active center more intuitively, we performed a wavelet transform on the EXAFS data to obtain the Fig.11It can be observed intuitively in the low frequency region There are Ni-N and Ni-C signals, high frequency area It shows the characteristics of Ni-Ni, and through the fitting of coordination bonds and coordination numbers, it is proved that the obtained catalyst has a Ni2N4C2 coordination structure.
[0019] The Ni diatomic electrocatalyst prepared by the present invention generates CO in the CO2 reduction reaction. The carbon paper loaded with the Ni diatomic electrocatalyst is used as the working electrode, the saturated silver / silver chloride electrode is used as the reference electrode, the platinum wire is used as the counter electrode, and the 0.5-2 mol / L potassium hydroxide solution is used as the electrolyte. The CO2 electroreduction reaction is carried out in a flow cell through a three-electrode system. Fig.12 As shown in Figure 2, at a low voltage of -0.25 V (vs. RHE), the catalyst can catalyze the reduction of CO2 to CO, and the Faraday efficiency (FE CO ) can be as high as 92.78% (such as Fig.13 ), maintaining a CO selectivity of more than 92.78% in an ultra-wide voltage window from -0.25V (vs.RHE) to -1.4V (vs.RHE), and at -1.0V (vs.RHE), FE CO Up to 99.2%, CO current density up to 123.32mA / cm 2 , reaching industrial-grade current density (100mA / cm 2 )(like Fig.12 , 14 ). In addition, the electrocatalyst also has good catalytic stability, such as Fig.15 In the 10-hour constant voltage test, the product FE CO Basically maintained above 97%.
[0020] The beneficial effects of the present invention are as follows: 1. The Ni diatomic electrocatalyst prepared by the method of the present invention has low-priced and readily available catalytic raw materials, a simple, economical and reproducible preparation process, is easy to mass-produce, and has good prospects for industrial application. 2. The Ni diatomic electrocatalyst prepared by the method of the present invention can obtain a catalyst with a Ni2N4C2 coordination structure by adjusting the raw material composition, reaction temperature and time. 3. The Ni diatomic electrocatalyst prepared by the method of the present invention can achieve highly selective electrocatalytic CO2 reduction to prepare CO at room temperature and pressure. At a low voltage of -0.25V (vs.RHE), the catalyst can catalyze the reduction of CO2 to CO, and the product CO Faraday efficiency (FE CO ) can be as high as 92.78%, and the CO selectivity is maintained above 92.78% in the ultra-wide voltage window from -0.25V (vs.RHE) to -1.4V (vs.RHE). When the reduction voltage is -1.0V (vs.RHE), the FECO Up to 99.2%, CO current density up to 123.32mA / cm 2 , reaching industrial-grade current density (100mA / cm 2 In addition, the electrocatalyst also has good catalytic stability. In the constant voltage test for 10 hours, the product FE CO Basically maintained above 97%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Scanning electron microscope image of the catalyst prepared in Example 1 of the present invention.
[0022] Figure 2 A high-angle annular dark-field scanning transmission electron microscopy image of the catalyst prepared in Example 1 of the present invention.
[0023] Figure 3 Spherical aberration corrected transmission electron microscopy image of the catalyst prepared in Example 1 of the present invention.
[0024] Figure 4 Element distribution diagram of the catalyst prepared in Example 1 of the present invention.
[0025] Figure 5 X-ray diffraction spectrum of the catalyst prepared in Example 1 of the present invention.
[0026] Figure 6 Raman spectrum of the catalyst prepared in Example 1 of the present invention.
[0027] Figure 7 X-ray photoelectron spectrum N1s orbital diagram of the catalyst prepared in Example 1 of the present invention.
[0028] Figure 8 X-ray photoelectron spectrum Ni2p orbital diagram of the catalyst prepared in Example 1 of the present invention.
[0029] Fig. 9 K-edge X-ray absorption spectrum of the catalyst prepared in Example 1 of the present invention.
[0030] Fig.10 Extended X-ray absorption fine structure R-space Fourier transform spectrum of the catalyst prepared in Example 1 of the invention.
[0031] Fig.11 Wavelet transform spectrum of the X-ray absorption spectrum of the catalyst prepared in Example 1 of the present invention.
[0032] Fig.12 LSV curve of the CO2 electro-reduction catalyst prepared in Example 1 of the present invention.
[0033] Fig.13A bar graph of the CO Faraday efficiency of the CO2 electro-reduction catalyst prepared in Example 1 of the present invention at different voltages.
[0034] Fig.14 CO partial current density curve of the CO2 electro-reduction catalyst prepared in Example 1 of the present invention.
[0035] Fig.15 Constant voltage stability test diagram of the CO2 electro-reduction catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described below by way of examples, but is not limited to the examples described.
[0037] Example 1
[0038] The cut nickel foam (Ni) of 2cm×2cm was soaked in anhydrous ethanol for ultrasonic cleaning, then rinsed with deionized water and placed in an oven for drying. Weigh 2g of dicyandiamide (DCD) on an electronic balance and place it in a porcelain boat. Place the porcelain boat containing DCD in the upstream position of the tube furnace, take out the nickel foam and place it in another porcelain boat and place it in the downstream position of the tube furnace. During the heating process of the tube furnace, 50sccm of argon (Ar) was used as the protective gas, the heating rate was 10℃ / min, the temperature was raised to 700℃ and kept for 1h, and then naturally cooled to room temperature. The product after the reaction was collected and marked as D-Ni-700. After sufficient grinding, it was soaked in 5mol / L (M) HCl for 80h to etch the nickel foam. It was then fully washed with deionized water, centrifuged at high speed, and collected after complete drying to obtain the Ni diatomic catalyst, marked as D-Ni-700-H. The catalyst was loaded on carbon paper as the working electrode, a saturated silver / silver chloride electrode was used as the reference electrode, a platinum wire was used as the counter electrode, and a 1 mol / L potassium hydroxide solution was used as the electrolyte, and the CO2 electroreduction reaction was carried out in a flow cell through a three-electrode system.
[0039] Example 2
[0040] The cut nickel foam (Ni) of 1cm×1cm was soaked in anhydrous ethanol for ultrasonic cleaning, then rinsed with deionized water and placed in an oven for drying. 3g of dicyandiamide (DCD) was weighed on an electronic balance and placed in a porcelain boat. The porcelain boat containing DCD was placed in the upstream position of the tube furnace, and the nickel foam was taken out and placed in another porcelain boat and placed in the downstream position of the tube furnace. During the heating process of the tube furnace, 100sccm of argon (Ar) was used as the protective gas, the heating rate was 5℃ / min, the temperature was raised to 750℃ and kept for 0.5h, and then naturally cooled to room temperature. The reaction product was collected, fully ground, and soaked in 3mol / L (M) HCl for 60h to etch the nickel foam. It was then fully washed with deionized water, centrifuged at high speed, and collected after complete drying to obtain the Ni diatomic catalyst, which was marked as D-Ni-750-H. The catalyst was loaded on carbon paper as the working electrode, a saturated silver / silver chloride electrode was used as the reference electrode, a platinum wire was used as the counter electrode, and a 0.5 mol / L potassium hydroxide solution was used as the electrolyte, and the CO2 electroreduction reaction was carried out in a flow cell through a three-electrode system.
[0041] Example 3
[0042] The cut nickel foam (Ni) of 1.5cm×1.5cm was soaked in anhydrous ethanol and ultrasonically cleaned, then rinsed with deionized water and placed in an oven to dry for use. 1g of dicyandiamide (DCD) was weighed on an electronic balance and placed in a porcelain boat. The porcelain boat containing DCD was placed upstream of the tube furnace, and the nickel foam was taken out and placed in another porcelain boat and placed downstream of the tube furnace. During the heating process of the tube furnace, 200sccm of argon (Ar) was used as the protective gas, the heating rate was 5℃ / min, the temperature was raised to 800℃ and kept warm for 2h, and then naturally cooled to room temperature. The reaction product was collected, fully ground, and soaked in 3mol / L (M) HCl for 48h to etch the nickel foam. It was then fully washed with deionized water, centrifuged at high speed, and collected after complete drying to obtain the Ni diatomic catalyst, which was marked as D-Ni-800-H. The catalyst was loaded on carbon paper as the working electrode, a saturated silver / silver chloride electrode was used as the reference electrode, a platinum wire was used as the counter electrode, and a 2 mol / L potassium hydroxide solution was used as the electrolyte, and the CO2 electroreduction reaction was carried out in a flow cell through a three-electrode system.
Claims
1. A nickel diatomic carbon dioxide electroreduction catalyst with a wide voltage window and a preparation method thereof, characterized in that: The electrocatalyst is a carbon nanotube with Ni diatomic active sites and uncoordinated nitrogen doped structure grown in situ on a nickel substrate by using a precursor gas phase transfer method at a certain temperature. The obtained catalyst exhibits a high CO selectivity of 92.78% for carbon dioxide electroreduction at a low voltage of -0.25V (vs.RHE), has high carbon dioxide electroreduction activity and high CO selectivity in a wide voltage window of about 1.2V, and reaches an industrial-grade current density (100mA / cm 2 ).
2. The preparation of the catalyst according to claim 1 specifically comprises the following steps: (1) cutting a certain size of nickel foam (Ni), soaking it in anhydrous ethanol and ultrasonic cleaning it, then rinsing it with deionized water and drying it in an oven for later use; (2) placing a certain amount of dicyandiamide (DCD) upstream of the tube furnace and placing nickel foam downstream of the tube furnace; (3) Using argon (Ar) as the protective gas, the tube furnace is heated to a certain temperature at an appropriate heating rate, and the temperature is maintained at the growth temperature for 0.2 to 3 hours, and then naturally cooled to room temperature; (4) collecting the product after the reaction, grinding it thoroughly, and then soaking and etching the nickel foam with HCl; (5) After the etching is completed, the product is taken out and washed thoroughly with deionized water, centrifuged at high speed, and collected after being completely dried to obtain the catalyst according to claim 1.
3. The method for preparing the nickel diatomic catalyst according to claim 2, characterized in that: During the preparation process, the purity of the nickel foam is 98% to 99.999%.
4. The method for preparing the nickel diatomic catalyst according to claim 2, characterized in that: During the preparation process, the purity of the dicyandiamide is 98% to 99.999%.
5. The method for preparing the nickel diatomic catalyst according to claim 2, characterized in that: During the preparation process, the argon gas flow rate is 30-300 sccm. The heating rate of the tubular furnace is 5-20°C / min.
6. The method for preparing the nickel diatomic catalyst according to claim 2, characterized in that: During the preparation process, the annealing temperature is 600° C. to 1000° C., and the insulation time is 0.2 to 3 hours.
7. The method for preparing the nickel diatomic catalyst according to claim 2, characterized in that: During the preparation process, the concentration of hydrochloric acid used in acid etching is 1-5 mol / L, the acid etching temperature is 60-80° C., and the acid etching time is 48-100 hours.
8. The use of the nickel diatomic catalyst according to claim 1 in the electroreduction of CO2 to generate CO, characterized in that: The carbon paper loaded with the Ni diatomic electrocatalyst is used as the working electrode, the saturated silver / silver chloride electrode is used as the reference electrode, the platinum wire is used as the counter electrode, and the 0.5-2 mol / L potassium hydroxide solution is used as the electrolyte. The CO2 electroreduction reaction is carried out in a flow cell through a three-electrode system. CO2 can be catalyzed to be reduced to CO at a low voltage of -0.25 V (vs. RHE), and the product CO Faraday efficiency (FE CO ) is as high as 92.78%, and the CO selectivity can be maintained above 92.78% in the ultra-wide voltage window from -0.25V (vs.RHE) to -1.4V (vs.RHE). When the reduction voltage is -1.0V (vs.RHE), the FE CO Up to 99.2%, CO current density up to 123.32mA / cm 2 , reaching industrial-grade current density (100mA / cm 2 ).
Citation Information
Patent Citations
Ni / N-CNTs catalyst for electrocatalytic CO2 reduction reaction and preparation method of Ni / N-CNTs catalyst
CN113322486A
Preparation method of catalyst with monatomic nickel anchored in nitrogen-doped carbon nanotube
CN118308749A
Monatomic nickel-loaded graphite phase carbon nitride material, preparation method and application of monatomic nickel-loaded graphite phase carbon nitride material in preparation of carbon monoxide by photocatalysis of carbon dioxide
CN118719119A